Contribution of Islamic Religious Education to Intercultural Values in Pluralistic European Cultures: Insights from Bosnia and Herzegovina - Sijamhodžić-Nadarević, Dina (Religions, 2023)
This article aims to highlight how Islamic Religious Education in Bosnia and Herzegovina, a country of rich cultural and religious diversity, promotes and advocates intercultural values of diversity, tolerance, solidarity, peace and dialogue in the context of contribution to intercultural values in pluralistic European cultures. This article also emphasizes the growing need to raise inclusive religious and intercultural awareness. Further, this article provides a content analysis of the BH unified curriculum of confessional Islamic Religious Education (IRE), a subject that is incorporated in all state-maintained schools, as well as the analyses of intercultural values embedded in Islamic higher education programs of the Faculty of Islamic Studies at the University of Sarajevo, which prepares religious education teachers and mu’allims. The purpose of this article is also to review the practices and projects which center around the intercultural and interreligious development of teachers and students through practical experience with intercultural dialogue.